Rotational Ground-State Bands of Doubly Even-Even 170,172Hf Isotopes - Hossain, I.; Y. Abdullah, Hewa; Ahmed, I.M.; Fadhil I. Sharrad, (International Journal of Scientific Research and Management (IJSRM), 2021)
Using phenomenological fitting, Sood’s semi-empirical formula have been investigated the rotational structure of even-even rare-earth 170,172Hf nuclei. The calculated rotational energies were compared with their corresponding experimental data. It showed that in 172Hf and 170Hf isotopes, calculated energies fits the experimental values to a remarkable degree of accuracy with deviation less than 3 percent at Jπ = 18+ state and Sood’s semi-empirical formula predicted rotational energies.